1995
DOI: 10.1183/09031936.95.08111825
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and pulmonary vascular response to hypoxia and susceptibility to high altitude pulmonary oedema

Abstract: Reduced tolerance to high altitude may be associated with a low ventilatory and an increased pulmonary vascular response to hypoxia. We therefore, examined whether individuals susceptible to acute mountain sickness (AMS) or high altitude pulmonary oedema (HAPE) could be identified by noninvasive measurements of these parameters at low altitude. Ventilatory response to hypoxia (HVR) and hypercapnia (HCVR) at rest and during exercise, as well as hypoxic pulmonary vascular response (HPVR) at rest, were examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
95
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 30 publications
13
95
2
1
Order By: Relevance
“…The crucial role of high pulmonary artery pressure is confirmed by elevated pulmonary artery pressures in patients with HAPE [2][3][4], enhanced pulmonary vasoconstrictive response in HAPE-susceptible subjects to acute hypoxia [5][6][7][8] or exercise in normoxia [6,7,9]. It is also confirmed by the fact that interventions decreasing pulmonary artery pressure are effective in the treatment [10,11] and prevention [4] of HAPE.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The crucial role of high pulmonary artery pressure is confirmed by elevated pulmonary artery pressures in patients with HAPE [2][3][4], enhanced pulmonary vasoconstrictive response in HAPE-susceptible subjects to acute hypoxia [5][6][7][8] or exercise in normoxia [6,7,9]. It is also confirmed by the fact that interventions decreasing pulmonary artery pressure are effective in the treatment [10,11] and prevention [4] of HAPE.…”
supporting
confidence: 59%
“…Most studies report positive associations [8,12,13], although one study found no relationship between HAPE and HVR [14]. Furthermore, some studies have reported associations between susceptibility to HAPE and lower vital capacity [8,9,15,16] or lower functional residual capacity [16].…”
mentioning
confidence: 99%
“…These blood gas changes might be due to a mild interstitial oedema not visible on chest radiographs [8], but suggested by a slight decrease of vital capacity and increase of closing volume [9,10]; however, these are inconsistent findings [11]. Furthermore, a lower ventilatory drive in hypoxia might contribute to more severe hypoxaemia in AMS, at least in some individuals [12,13]. Laboratory investigations of the brain in AMS show that all subjects exposed to altitudes of 4500 m had normal lumbar cerebrospinal fluid pressure and a small increase of brain volume assessed using MRI (<1%, ∼7-10 mL) after 16 h, independent of presence or absence of AMS [14].…”
Section: Ams and Hacementioning
confidence: 99%
“…They have lower HVR [12,67] and stronger sympathetic tone [68]. HVR is set largely by the peripheral chemoreceptors, which results in a lower alveolar oxygen tension and higher carbon dioxide tension at the same altitude as HAPE-resistant subjects, and thus leads to a stronger stimulus for HPV [69].…”
Section: Haemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation